A Meta-Analysis and Systematic Review of the Efficacy of Twice Daily PPIs versus Once Daily for Treatment of Gastroesophageal Reflux Disease. (22nd August 2017) - Zhang, Hongying; Yang, Zhiping; Ni, Zhen; Shi, Yongquan
Abstract : Background. To investigate whether PPIs BID is superior to QD for treatment of GERD in a short time. Methods. We searched PubMed, Cochrane Library, Scopus, EMBASE, Ovid, EBSCO, and Web of Science databases (from 1998 to May 2016) to select RCTs, which compared the efficacy of PPIs BID versus QD for GERD. The primary outcomes were symptom relief or esophageal mucosal healing at weeks 4 and 8. The M-H method with fixed-effect or random-effect model was used to calculate RR and 95% CIs. Results. Seven RCTs were enrolled. The esophageal healing rates were higher in PPIs BID group (P = 0.01 ), and rabeprazole 20 mg BID can achieve better mucosal healing than 20 mg QD after 8 weeks (P < 0.05 ). However, no significant differences were observed in heartburn relief (P = 0.27 ), sustained symptom relief rates at week 4 (P = 0.05 ), 24 h pH monitoring after treatment (P = 0.11 ), endoscopic response at week 4 (P = 0.22 ), and adverse events (P = 0.18 ). Conclusion. PPIs BID more effectively improve endoscopic healing rate at week 8 than PPIs QD. But there are no significant differences in symptom relief, 24 h pH monitoring, sustained symptom relief, and endoscopic response at week 4.